Social interaction in learning styles and English language anxiety among pre-servive teachers - Yap, Soon Li (Universiti Malaysia Sarawak (UNIMAS), 2015)
This research investigates the significance association between social interaction learning style and English language anxiety among pre-service teachers. The following basis demographic variables were included in the study: gender, ethnicity, and academic major. English proficiency level based on self-perception identified as covariate variable was also included in the research. A one-shot cross-sectional survey with correlational and comparative research design was used to explore the association.